2019
DOI: 10.1128/jvi.01400-18
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Restriction-Like Gene drl-1 , Which Encodes a Putative Serine/Threonine Kinase, Is Essential for Orsay Virus Infection in Caenorhabditis elegans

Abstract: Orsay virus is the only known natural virus pathogen of Caenorhabditis elegans, and its discovery has enabled virus-host interaction studies in this model organism. Host genes required for viral infection remain understudied. We previously established a forward genetic screen based on a virus-inducible green fluorescent protein transcriptional reporter to identify novel host factors essential for virus infection. Here, we report the essential role in Orsay virus infection of the dietary restriction-like (drl-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…The two hipr-1 mutant alleles identified in this study phenocopy the viral replication and GFP induction defects observed in the previously identified essential C. elegans host gene mutant alleles sid-3 , viro-2 , and nck-1 ( 2 ). As the human orthologs of sid-3 , viro-2 , and nck-1 have since been demonstrated to function in a pathway ( 3 ), it is intriguing to speculate that hipr-1 may also be part of this pathway. However, as all mutant alleles represent null function for Orsay virus infection in C. elegans , any genetic endeavor to reveal their relationship remains challenging in C. elegans .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two hipr-1 mutant alleles identified in this study phenocopy the viral replication and GFP induction defects observed in the previously identified essential C. elegans host gene mutant alleles sid-3 , viro-2 , and nck-1 ( 2 ). As the human orthologs of sid-3 , viro-2 , and nck-1 have since been demonstrated to function in a pathway ( 3 ), it is intriguing to speculate that hipr-1 may also be part of this pathway. However, as all mutant alleles represent null function for Orsay virus infection in C. elegans , any genetic endeavor to reveal their relationship remains challenging in C. elegans .…”
Section: Discussionmentioning
confidence: 99%
“…The multicellular model organism Caenorhabditis elegans is naturally infected by Orsay virus, a positive-sense, nonenveloped RNA virus ( 1 ). This infection system has recently been utilized to identify several novel host factors that are essential for Orsay virus infection ( 2 , 3 ). Through an unbiased forward genetic screen, the genes sid-3 , viro-2 , and drl-1 were previously identified as host factors essential at an early stage of the Orsay virus life cycle ( 2 , 3 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Table S4 Genes involved during OrV infection -Overview of C. elegans genes involved in OrV infection described in literature. Data is obtained from Bakowski et al 2014;Chen et al 2017;Félix et al 2011;Frézal et al 2019;Jiang et al 2017;Le Pen et al 2018;Reddy et al 2017Reddy et al , 2019Sandoval et al 2019;Sarkies et al 2013;Sowa et al 2019;Sterken et al 2014;Tanguy et al 2017).…”
mentioning
confidence: 99%